Dual DNA Barcoding for the Molecular Identification of the Agents of Invasive Fungal Infections - Hoang, Minh Thuy Vi; Irinyi, Laszlo; Chen, Sharon C. A.; Sorrell, Tania C.; , The ISHAM Barcoding of Medical Fungi Working Group; Meyer, Wieland; Arabatzis, Michael; Arthur, Ian; Cano-Lira, Jose F.; Cardinali, Gianluigi; Castañón, Laura Rosio; Chen, Sharon; et al. (Frontiers in Microbiology, 2019)
Invasive fungal infections, such as aspergillosis, candidiasis and cryptococcosis, have significantly increased among immunocompromised people. To tackle these infections the first and most decisive step is the accurate identification of the causal pathogen. Routine identification of invasive fungal infections has progressed away from culture-dependent methods towards molecular techniques, including DNA barcoding, a highly efficient and widely used diagnostic technique. Fungal DNA barcoding previously relied on a single barcoding region, the internal transcribed spacer region (ITS). However, this allowed only for 75% of all fungi to be correctly identified. As such, the translational elongation factor 1α (TEF1α) was recently introduced as the secondary barcode region to close the gap. Both loci together form the dual fungal DNA barcoding scheme. As a result, the ISHAM Barcoding Database has been expanded to include sequences for both barcoding regions to enable practical implementation of the dual barcoding scheme into clinical practice. The present study investigates the impact of the secondary barcode on the identification of clinically important fungal taxa, that have been demonstrated to cause severe invasive disease. Analysis of the barcoding regions was performed using barcoding gap analysis based on the genetic distances generated with the Kimura 2-parameter model. The secondary barcode demonstrated an improvement in identification for all taxa that were unidentifiable with the primary barcode, and when combined with the primary barcode ensured accurate identification for all taxa analyzed, making DNA barcoding an important, efficient and reliable addition to the diagnostic toolset of invasive fungal infections.